Supply Chain Management Practice and Competitive Advantage: Systematic Literature Review - Alemgenet Hailu Menesha; Ethel Tembo Mwanaumo (Research Synergy Press, 2023)
Supply chain management integrates activities through improved supply chain relationships to achieve sustainable competitive advantage. The major objective of the study is to review academic articles published previously concerning the relationship between supply chain management practices and competitive advantage to indicate a direction that could need further research. This review adopts the systematic literature review approach to identify studies conducted between 2002 and 2022. The review focused on summarizing the studies' major aspects and analyzing them by identifying themes. The paper identified 25 most impactful studies in this area. The finding indicates that most studies were empirical studies and used a quantitative research approach with an explanatory research design. The analysis of the papers demonstrated that the Resource-Based Theory, Dynamic Capability Theory, Resource Dependency Theory, Relational View, Knowledge–based Theory, and System Theory are among the major theories used as a foundation for the studies. Supply chain management dimensions such as strategic supplier partnership, customer relationship, information sharing, quality of information, and postponement are used to measure Supply chain management practices. Furthermore, price/cost, product innovation, time to market, delivery, and Dependability are used to predict Competitive advantage